A shared register specification as the source of complete Modbus RTU device support - Świtalski, Emilian; Górecki, Krzysztof (International Journal of Electronics and Telecommunications, 2026)
Since 1979, Modbus RTU has remained one of the most popular industrial communication protocols, yet it carries no information about the meaning of the registers it transmits. As a result, the same description (type, unit, range, factory value) appears in parallel across the device firmware, the client software, the user interface, and the documentation. This article presents an approach in which a single CSV text file serves as a shared source of truth for all layers that handle a device. We describe the concept of a register descriptor together with its implementation in the open-source application Modra, which runs both as a desktop program and as an HTTP server. The application was verified on a case study controlling the inverter of a permanent-magnet synchronous motor (PMSM).